Gene and dietary calcium interaction effects on brachial–ankle pulse wave velocity. Issue 5 (October 2016) - Choi, SeongIl; Jung, Sukyoung; Kim, Mi Kyung; Shin, Jinho; Shin, Min-Ho; Shin, Dong Hoon; Lee, Young-Hoon; Chun, Byung-Yeol; Hong, Kyung-Won; Hwang, Joo-Yeon
Summary: Background & aim: Understanding the lifestyle and genetic factors that affect pulse wave velocity (PWV) may provide clues to preventing atherosclerotic cardiovascular events. The aim of this study is to investigate genome-wide genetic and dietary calcium (Ca) intake interaction effects on brachial–ankle pulse wave velocity (baPWV). Methods: The baPWV was measured, and Ca intake was quantified by administering a food frequency questionnaire (FFQ) to 3198 participants, which included men and women (≥40 years) from the KoreanM ulti-R ural communitiesCohort study (MRCohort). The interaction effects of dietary Ca intake and 19 single-nucleotide polymorphisms (SNPs) on baPWV were assessed using the general linear models. Results: Dietary Ca intake was not significantly associated with baPWV or any type of SNP among the subjects herein. In men, however, the adducin1 (ADD1) rs4961_C SNP had a significant dietary Ca intake–dependent effect on mean baPWV ( p interaction = 0.002). In women, the interaction of zinc finger proteins 618 (ZNF618) rs10817542_A with dietary Ca intake played a significant and key role in mean baPWV ( p interaction = 0.001). In the results of ADD1 rs4961_C in men and ZNF618 rs10817542_A in women, the minor allele-lowest Ca intake tertile (T1) group had significantly higher mean baPWV value than other subgroups of Ca intake tertile-genotype cross-classification whereas genotype was not a significant effector on mean baPWV values among highest Ca intake subgroups (T3). Conclusions: The baPWV, a phenotype of arterial stiffness, can be modulated in subjects through regulation of dietary Ca intake, particularly in subjects with more vulnerable genotypes.